In-process Profiling of Herbomineral Formulation from Marine Origin - Rasheed, Shebina P.; Shivashankar, Murugesh (Jordan Journal of Pharmaceutical Sciences, 2023)
Objectives: To prepare Shankha Bhasma, an antiulcer formulation from marine origin and to standardize the formulation by two different methods of preparation and to compare with marketed formulation by modern scientific tools Methods: Shankha Bhasma was prepared from conch shell by open and closed methods using adjuvants Kumari Swarasa and water and subjected to characterization by conventional method and AAS, XRD, EDAX, SEM, TEM, BET, TGA, IR spectroscopy. The effectiveness was checked by animal studies, toxicity by histopathology and cytotoxicity studies. Results: Open method takes few steps and less time and shows crystalline nature (XRD).TGA shows the decomposition temp of calcium oxide. The closed method produces smoother particle (SEM,TEM and BET) with no peaks for specific organic components (IR), elements within the prescribed limits (AAS) of Ayurveda. The adjuvant’s effectiveness was shown by in-process standardization and showed promising pharmacological effects without any toxic effects the dose selected was 25mg to 50mg Conclusions: The size, smoother surface and therapeutic effectiveness of the herbominerals prepared by the two methods can be attributed to the calcination steps and adjuvants. Thus, maybe dose reduction and rapid effect can be achieved.